Routine DNA cytometry of benign and malignant pleural effusions by means of the remote quantitation server Euroquant: a prospective study. Issue 10 (1st October 2000) - Kayser, K; Blum, S; Beyer, M; Haroske, G; Kunze, K D; Meyer, W
Abstract : Aim —To analyse the practicability and potential assistance of static DNA cytometry performed by means of the remote quantitation server Euroquant and the internet in routine diagnostic analysis of pleural effusions, and to outline the role of DNA cytometry on pleural effusions in distinguishing between benign and malignant (and herein primary versus metastatic) effusions. Materials and methods— Cytological smears of 294 pleural effusions were stained with the Feulgen method. The DNA content of a minimum of 300 randomly chosen analysis nuclei and 30 reference nuclei (lymphocytes) was measured by internet connection to the remote quantitation server Euroquant. Cytometric features were derived from the histograms, and the time needed for case evaluation, the reliability of staining and measurement procedures, and the contribution to the final diagnosis were evaluated. Results —Only 120 of 294 pleural effusions could be measured. The total measurement time for each specimen was 60 minutes. The guidelines of the consensus report on DNA measurements were fulfilled. Seventy eight malignant (18 mesotheliomas, 60 metastatic tumours) and 42 benign effusions were measured. Seven of 78 malignant effusions were euploid and none of 42 benign effusions were aneuploid. The sensitivity and specificity were 91% and 100%, respectively, for distinguishing benign from malignant effusions, and 95% and 100%, respectively, for discriminating between benign and malignant effusions caused by metastatic malignant tumours. Conclusions —Static DNA cytometry using the remote quantitation server Euroquant can be performed reliably in the routine diagnosis of pleural effusions; however, only 40% of effusions meet the technical requirements for static DNA cytometry. Within the measurable cases, static DNA cytometry made an important contribution to the confirmation/exclusion of malignancy.